STRATEGI INDONESIA DALAM MENINGKATKAN EKSPOR BAWANG MERAH KE THAILAND TAHUN 2016-2020 - Yulia Bakri; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study describes Indonesia's strategy in increasing shallot exports to Thailand. Shallots are exported to several countries such as Thailand, Singapore, Malaysia, Japan and Taiwan. And Indonesia's main and largest export destination for shallots is Thailand. Various obstacles were experienced by Indonesia to export shallots to Thailand, where the shallot products exported by Indonesia were also produced by Thailand.The author collects data from books, academic journals, mass media, and sources from the Internet related to the issue of this research which discusses Indonesia's strategy in increasing shallot exports to Thailand. The author uses the perspective of liberalism and country-level analysis. The theory used in this research is the theory of competitive advantage theory from Michael E. Porter.This study found that Indonesia in increasing exports of shallots to Thailand by increasing the cooperation of Indonesia's trade attache in Thailand with the Thai government in improving the quality standards of shallots required by Thailand, conducting promotions through international trade fairs in Thailand to highlight the advantages of shallot products from Indonesia, and conducting negotiations between the Indonesian government and the Thai government through the Joint Commission Meeting (JCM) on the implementation of Thailand's shallot import policy.Keywords: Strategy, Shallots, Exports, Joint Agriculture Working Group.